AI- A Distance Learning Tool - Chen, Xuelian; Yang, Yang; Xie, Jin (LPPM STIKI Malang, 2024)
With the development of information technology, artificial intelligence (AI) has shown great potential in the field of distance learning. This article focuses on AI as a distance learning tool and explores its intelligent learning assistance features, including providing students with personalized learning paths, real-time Q&A, and more. It also explains the role of AI in the generation and optimization of teaching content, such as using technology to generate high-quality course text and materials, and optimizing content based on feedback. Research shows that AI is revolutionizing remote learning and can dramatically improve learning outcomes.